One Earth-One Health (OE-OH): Antibacterial Effects of Plant Flavonoids in Combination with Clinical Antibiotics with Various Mechanisms - Ganjun Yuan; Fengxian Lian; Yu Yan; Yu Wang; Li Zhang; Jianping Zhu; Aiman Fatima; Yuxing Qian (Antibiotics)
Background/Objectives: Antimicrobial resistance (AMR) poses a significant threat to human health, and combination therapy has proven effective in combating it. It has been reported that some plant flavonoids can enhance the antibacterial effects of antibiotics and even reverse AMR. This study systematically evaluated the synergistic effects of plant flavonoids and clinical antibiotics. Methods: The antibacterial activities of thirty-seven plant flavonoids and nine clinical antibiotics with various antimicrobial mechanisms were determined using the microbroth dilution method. Subsequently, the combined effects of twelve plant flavonoids presenting definite MICs against Staphylococcus aureus with these nine antibiotics were determined using the checkerboard test, together with those of thirty-two plant flavonoids presenting definite MICs against Escherichia coli with these nine antibiotics. Results: Plant flavonoids in combination with antibiotics present extensive synergistic effects, and 25% of combinations exhibited synergy against S. aureus and 50% against E. coli, particularly with antibiotics affecting cell membranes or ribosomes. Conclusions: The findings align with the drug selection principle of synergistic combinations and suggest that plant flavonoids could extensively enhance antibiotic efficacy. Considering that various metabolites from microorganisms, plants, and animals on the Earth would definitely impact the evolution of AMR, together with the rules, key factors, and important principles of drug combination for preventing AMR, we further propose the “One Earth-One Health (OE-OH)” concept, emphasizing ecosystem interactions in AMR prevention.